The Relationship Between Knowledge and Attitudes Toward Oral and Dental Health and Hygiene and the Incidence of Gingivitis Among Elementary School Children - Akbar, Ilham Fahmi (Sean Institute, 2025)
Oral and dental health is an essential aspect of overall health, particularly in elementary school-aged children who are in their developmental stages. Gingivitis, or gum inflammation, is a common oral disease among children and can be prevented through proper knowledge and positive attitudes toward oral hygiene. This study aims to examine the relationship between knowledge and attitudes about oral health and hygiene with the incidence of gingivitis among fifth-grade students at SDN Dukuh Kupang V Surabaya. This analytic quantitative research used a cross-sectional approach and involved 63 respondents. Data were collected through questionnaires and analyzed using the Chi-Square test. The results showed a significant relationship between students' knowledge and attitudes toward oral health and the incidence of gingivitis (p < 0.001). Students with better knowledge and attitudes were less likely to suffer from gingivitis. These findings highlight the importance of early education and the development of healthy habits to prevent periodontal diseases.